Nanoporous aramid nanofiber membrane with high modulus and thermal stability

By introducing nanoporous aramid nanofiber and microfluidic continuous printing technology in the preparation process of lithium-ion battery separators, the problem of insufficient structural and mechanical stability of traditional separators at high temperatures is solved, and a high modulus and thermal stability separator is achieved, which improves the safety and performance of the battery.

CN119786875APending Publication Date: 2025-04-08SHAANXI SHENGSHI CHENYANG TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510215973.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators are prone to heat shrinkage or melting at high temperatures, resulting in short circuits inside the battery, and insufficient modulus cannot effectively resist the growth of lithium dendrites, affecting the safety of the battery.

Method used

The nanoporous aramid nanofiber separator is adopted to accurately control the pore size and thickness of the separator through microfluidic continuous printing technology and double-sided solvent diffusion process, optimize the microstructure, and improve mechanical performance and thermal stability.

Benefits of technology

Maintain structural and mechanical stability in high temperature environments, significantly improve the modulus, thermal stability and breathability of the diaphragm, and enhance the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786875A_ABST
    Figure CN119786875A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material science, and discloses a nano-porous aramid nanofiber diaphragm with high modulus and thermal stability, para-aramid with the purity greater than 99% is selected as a base material, an N-methyl pyrrolidone solvent is added into a reaction kettle, then the para-aramid is added into the reaction kettle in three batches, and the para-aramid nanofiber diaphragm is prepared by the following steps: adding the para-aramid into the reaction kettle in three batches; carrying out low-temperature solution polycondensation reaction to form a uniform para-aramid solution, constructing a microfluid continuous printing device, setting parameters of the microfluid continuous printing device, carrying out printing to obtain a primary nanofiber diaphragm, constructing a double-sided solvent diffusion device, controlling diffusion process parameters, carrying out double-sided solvent diffusion, and after the double-sided solvent diffusion is completed, carrying out high-temperature drying to obtain the nanofiber diaphragm. According to the present invention, the nanometer fiber diaphragm is subjected to post-treatment, the performance characteristics and the existing problems of the nanometer fiber diaphragm are analyzed according to the test result, the improvement measures are provided according to the problems, and the nanometer porous aramid fiber nanometer fiber diaphragm prepared according to the process has the advantage of maintaining the structure and the mechanical stability at the high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material science, in particular to a nano porous aramid nano fiber diaphragm with high modulus and thermal stability. Background Art

[0002] In existing lithium-ion battery technology, especially under high temperature conditions, traditional diaphragm materials often fail to exhibit good structural and mechanical stability. For example, commonly used polyolefin diaphragms are prone to thermal shrinkage or even melting at high temperatures, resulting in internal short circuits in the battery, thereby inducing thermal runaway. In addition, under transient thermal abuse conditions, lithium batteries cannot effectively resist the growth of lithium dendrites due to the insufficient modulus of the diaphragm, further exacerbating the safety issues of the battery. Therefore, the development of a diaphragm material that can maintain structural and mechanical stability at high temperatures and has high modulus and excellent thermal stability is crucial to improving the safety and performance of lithium batteries. Based on this, nanoporous aramid nanofiber diaphragms came into being, which exhibit excellent thermal stability and mechanical properties due to the high strength, high modulus and high temperature resistance of aramid fibers. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the shortcomings of the prior art, the present invention provides a nanoporous aramid nanofiber diaphragm with high modulus and thermal stability, which has the advantages of maintaining structural and mechanical stability at high temperatures, solving the problem that traditional diaphragm materials often fail to exhibit good structural and mechanical stability.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a nanoporous aramid nanofiber membrane with high modulus and thermal stability, comprising the following preparation steps:

[0007] Step 1: Material preparation: Select para-aramid with a purity greater than 99% as the base material;

[0008] Step 2, preparing a para-aramid solution: adding N-methylpyrrolidone solvent into a reaction kettle, and then adding the para-aramid into the reaction kettle in three batches, and performing a low-temperature solution polycondensation reaction to form a uniform para-aramid solution;

[0009] Step 3: Formulate a microfluidic continuous printing strategy: construct a microfluidic continuous printing device, set the parameters of the microfluidic continuous printing device, perform printing, and obtain a preliminary nanofiber membrane;

[0010] Step 4: Design a double-sided solvent diffusion process: build a double-sided solvent diffusion device, control the diffusion process parameters, perform double-sided solvent diffusion, and perform post-processing on the nanofiber membrane after completing the double-sided solvent diffusion;

[0011] Step 5: Result analysis and optimization: Analyze the performance characteristics and existing problems of the nanofiber membrane based on the test results, and propose improvement measures to address the problems.

[0012] Preferably, the preparation process of the para-aramid solution in step 2 is:

[0013] S2.1, adding N-methylpyrrolidone solvent into the reaction kettle;

[0014] S2.2, lowering the solvent temperature to between -10°C and -5°C, adding the para-aramid in three batches, and carrying out a low-temperature solution polycondensation reaction for 2-4 hours under magnetic stirring;

[0015] S2.3. After the para-aramid is completely added, raise the temperature to between 55-60°C and continue to maintain magnetic stirring for 1-1.5 hours to form a uniform para-aramid solution.

[0016] Preferably, the microfluidic continuous printing device in step three includes a precision injection pump, a microfluidic chip and a collector, and the parameters of the microfluidic continuous printing device are set as follows: the thickness of the nanofiber diaphragm is set between 1.8-2.2μm, with an accuracy of ±0.1μm, the pore size of the nanofiber diaphragm is set between 40-60nm, with an accuracy of ±5nm, the flow rate of the injection pump is set to 2-3mL / h, the channel width of the microfluidic chip is set to 100-200μm, and the channel depth of the microfluidic chip is set to 50-100μm.

[0017] Preferably, the printing process in step 3:

[0018] S3.1. After the parameters of the microfluidic continuous printing device are set, the para-aramid solution is injected into the microfluidic chip through a syringe pump;

[0019] S3.2, controlling the flow rate of the para-aramid solution between 45-55 μL / min, controlling the temperature between 55° C. and 60° C., controlling the pressure difference between 20 psi and 25 psi, and adopting a laminar flow mode to form nanofibers using microfluidic technology;

[0020] S3.3. Collect the formed nanofibers through a collector to obtain a preliminary nanofiber membrane.

[0021] Preferably, the double-sided solvent diffusion device in step 4 comprises a solvent evaporation pool and a supporting substrate.

[0022] Preferably, the diffusion process parameters in step 4 are set as follows: the diffusion temperature is controlled between 55-60° C., and the diffusion time is controlled between 1.5-2 h.

[0023] Preferably, the diffusion process in step 4 is:

[0024] S4.1, selecting N,N-dimethylacetamide and dimethyl sulfoxide as solvents;

[0025] S4.2, placing the initially obtained nanofiber membrane in a double-sided solvent diffusion device;

[0026] S4.3. Place two different solvents of S4.1 on the upper and lower sides of the nanofiber membrane in the double-sided solvent diffusion device, and control the evaporation rate of the solvent to be between 0.3-0.5 mm / h, the evaporation direction of the solvent is perpendicular to the membrane surface, and control the ambient humidity to be between 30% and 40%.

[0027] Preferably, N,N-dimethylacetamide solvent is placed on the upper side of the nanofiber membrane, and dimethyl sulfoxide solvent is placed on the lower side of the nanofiber membrane.

[0028] Preferably, the concentration of the N,N-dimethylacetamide is 50% to 55%, and the concentration of the dimethyl sulfoxide is 30% to 35%.

[0029] Preferably, in the post-treatment process of step 4: after the double-sided solvent diffusion is completed, the nanofiber membrane is washed with deionized water for 2-5 times, and placed in an oven to dry at a temperature of 60-65° C. for 1-1.2 hours.

[0030] Compared with the prior art, the present invention provides a nanoporous aramid nanofiber membrane with high modulus and thermal stability, which has the following beneficial effects:

[0031] 1. The present invention introduces microfluidic continuous printing technology and double-sided solvent diffusion process into the preparation process of the diaphragm, and accurately controls the pore size and thickness of the diaphragm according to the flow rate, temperature and pressure difference. In the microfluidic continuous printing step, by adjusting the flow rate, temperature and pressure difference of the syringe pump, the deposition rate and morphology of the nanofibers can be accurately controlled, thereby affecting the pore size and thickness of the final diaphragm, and the microstructure can be optimized according to the type, concentration, evaporation rate and ambient humidity of the solvent. By selecting different concentrations of N,N-dimethylacetamide (DMAc) and dimethyl sulfoxide (DMSO) as solvents and controlling their evaporation rates and ambient humidity, the arrangement and fusion degree of the nanofibers can be further regulated, thereby optimizing the microstructure of the diaphragm to improve the mechanical properties, thermal stability and air permeability of the diaphragm. The above advantages enable the diaphragm prepared by the method of the present invention to exhibit excellent structure and mechanical stability in a high temperature environment, solving the shortcomings of traditional diaphragm materials and preparation processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A flow chart was prepared for the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] See also Figure 1 , a nanoporous aramid nanofiber separator with high modulus and thermal stability, comprising the following preparation steps:

[0035] Step 1: Material preparation: Select para-aramid with a purity greater than 99% as the base material. Its molecular weight should be greater than 100,000, with high strength, high modulus and excellent thermal stability (temperature resistance > 200°C) to ensure the performance of the final diaphragm;

[0036] Step 2, preparing a para-aramid solution: adding N-methylpyrrolidone (NMP) solvent into a reactor, and then adding the para-aramid into the reactor in three batches, and performing a low-temperature solution polycondensation reaction to form a uniform para-aramid solution, so as to ensure that the para-aramid is fully dissolved, and at a certain temperature and reaction time, a polycondensation reaction occurs between the para-aramid molecules to form a polymer chain, and a diaphragm with a specific structure and performance can be obtained by controlling the reaction conditions;

[0037] Step 3: Formulate a microfluidic continuous printing strategy: construct a microfluidic continuous printing device, set the parameters of the microfluidic continuous printing device, perform printing, and obtain a preliminary nanofiber (ANF) diaphragm;

[0038] Step 4: Design a double-sided solvent diffusion process: build a double-sided solvent diffusion device, control the diffusion process parameters, perform double-sided solvent diffusion, and after completing the double-sided solvent diffusion, post-treat the nanofiber (ANF) membrane;

[0039] Step 5. Result analysis and optimization: Analyze the performance characteristics and existing problems of the nanofiber (ANF) membrane based on the test results, and propose improvement measures for the problems, such as adjusting the parameters of the microfluidic continuous printing strategy and optimizing the conditions of the double-sided solvent diffusion technology.

[0040] Specifically, the preparation process of the para-aramid solution in step 2 is as follows:

[0041] S2.1, adding N-methylpyrrolidone (NMP) solvent into the reaction kettle;

[0042] S2.2, lowering the solvent temperature to between -10°C and -5°C, adding the para-aramid in three batches, and carrying out a low-temperature solution polycondensation reaction for 2-4 hours under magnetic stirring;

[0043] S2.3. After the para-aramid is completely added, the temperature is raised to between 55-60°C and the magnetic stirring is continued for 1-1.5 hours to form a uniform para-aramid solution to ensure that the para-aramid is fully dissolved.

[0044] Specifically, the microfluidic continuous printing device in step three includes a precision injection pump, a microfluidic chip and a collector to ensure the stability and accuracy of the device. The parameters of the microfluidic continuous printing device are set as follows: the thickness of the nanofiber membrane is set between 1.8-2.2μm, with an accuracy of ±0.1μm, the pore size of the nanofiber membrane is set between 40-60nm, with an accuracy of ±5nm, the flow rate of the injection pump is set to 2-3mL / h, the channel width of the microfluidic chip is set to 100-200μm, and the channel depth of the microfluidic chip is set to 50-100μm. The setting of the above parameters can achieve precise control of the flow thickness to the micron level.

[0045] Specifically, the printing process in step 3:

[0046] S3.1. After the parameters of the microfluidic continuous printing device are set, the para-aramid solution is injected into the microfluidic chip through a syringe pump;

[0047] S3.2, controlling the flow rate of the para-aramid solution between 45-55 μL / min, controlling the temperature between 55° C. and 60° C., controlling the pressure difference between 20 psi and 25 psi, and adopting a laminar flow mode to form nanofibers using microfluidic technology;

[0048] S3.3. Collect the formed nanofibers through a collector to obtain a preliminary nanofiber (ANF) separator.

[0049] Specifically, the double-sided solvent diffusion device in step 4 includes a solvent evaporation pool and a supporting substrate to ensure the uniformity and stability of the nanofiber (ANF) membrane during the diffusion process.

[0050] Specifically, the diffusion process parameters in step 4 are set as follows: the diffusion temperature is controlled between 55-60° C., and the diffusion time is controlled between 1.5-2 h.

[0051] Specifically, the diffusion process in step 4 is:

[0052] S4.1, select N,N-dimethylacetamide (DMAc) and dimethyl sulfoxide (DMSO) as solvents;

[0053] S4.2, placing the initially obtained nanofiber (ANF) membrane in a double-sided solvent diffusion device;

[0054] S4.3. Place two different solvents of S4.1 on the upper and lower sides of the nanofiber (ANF) membrane in a double-sided solvent diffusion device, and control the evaporation rate of the solvent to be between 0.3-0.5 mm / h. The evaporation direction of the solvent is perpendicular to the membrane surface, and the ambient humidity is controlled between 30% and 40%, thereby achieving uniform and controllable pore size.

[0055] Specifically, N,N-dimethylacetamide (DMAc) solvent is placed on the upper side of the nanofiber (ANF) membrane, and dimethyl sulfoxide (DMSO) solvent is placed on the lower side of the nanofiber (ANF) membrane.

[0056] Specifically, the concentration of N,N-dimethylacetamide (DMAc) is 50% to 55%, and the concentration of dimethyl sulfoxide (DMSO) is 30% to 35%.

[0057] Specifically, in the post-processing process of step 4: after completing the double-sided solvent diffusion, the nanofiber (ANF) diaphragm is washed with deionized water for 2-5 times, and placed in an oven and dried at a temperature of 60-65°C for 1-1.2h to remove residual solvent and improve material properties.

[0058] The advantages are: the present invention introduces microfluidic continuous printing technology and double-sided solvent diffusion process into the preparation process of the diaphragm, and accurately controls the pore size and thickness of the diaphragm according to the flow rate, temperature and pressure difference. In the microfluidic continuous printing step, the deposition rate and morphology of the nanofibers can be accurately controlled by adjusting the flow rate, temperature and pressure difference of the injection pump, thereby affecting the pore size and thickness of the final diaphragm, and the microstructure can be optimized according to the type, concentration, evaporation rate and ambient humidity of the solvent. By selecting N,N-dimethylacetamide (DMAc) and dimethyl sulfoxide (DMSO) of different concentrations as solvents and controlling their evaporation rates and ambient humidity, the arrangement and fusion degree of the nanofibers can be further regulated, thereby optimizing the microstructure of the diaphragm to improve the mechanical properties, thermal stability and air permeability of the diaphragm. The above advantages enable the diaphragm prepared by the method of the present invention to exhibit excellent structure and mechanical stability in a high temperature environment, solving the shortcomings of traditional diaphragm materials and preparation processes.

[0059] Example 1

[0060] Step 1: Material preparation: Para-aramid purity: 99.5%, molecular weight: 120,000, temperature resistance: >200°C;

[0061] Step 2: Prepare para-aramid solution:

[0062] S2.1: Add NMP solvent to the reactor;

[0063] S2.2: Lower the solvent temperature to -8°C, add the para-aramid in three batches, and stir magnetically for 3 hours;

[0064] S2.3: After complete addition, heat to 58°C and continue stirring for 1.2 hours to form a uniform solution;

[0065] Step 3: Microfluidic Continuous Printing:

[0066] S3.1: injecting the para-aramid solution into the microfluidic chip through a syringe pump;

[0067] S3.2: Control the flow rate to 50 μL / min, the temperature to 58 °C, the pressure difference to 22 psi, and the laminar flow mode;

[0068] S3.3: Collect the formed nanofibers to obtain a preliminary separator;

[0069] Step 4: Double-sided solvent diffusion:

[0070] S4.1: DMAc (52% concentration) and DMSO (32% concentration) were selected as solvents;

[0071] S4.2: placing the nanofiber membrane in a diffusion device;

[0072] S4.3: DMAc was placed on the upper side of the membrane and DMSO was placed on the lower side, the evaporation rate was 0.4 mm / h, the ambient humidity was 35%, the diffusion temperature was 58 °C, and the diffusion time was 1.8 hours;

[0073] Step 5: Post-treatment: Wash with deionized water for 3 times and dry at 62°C for 1.1 hours.

[0074] Example 2

[0075] Step 1: Material preparation: Para-aramid purity: 99.8%, molecular weight: 150,000, temperature resistance: >200°C;

[0076] Step 2: Prepare para-aramid solution:

[0077] S2.1: Add NMP solvent to the reactor;

[0078] S2.2: Lower the solvent temperature to -6°C, add the para-aramid in three batches, and stir magnetically for 2.5 hours;

[0079] S2.3: After complete addition, heat to 56°C and continue stirring for 1.3 hours to form a uniform solution;

[0080] Step 3: Microfluidic Continuous Printing:

[0081] S3.1: injecting the para-aramid solution into the microfluidic chip through a syringe pump;

[0082] S3.2: Control the flow rate to 52 μL / min, the temperature to 57 °C, the pressure difference to 23 psi, and use the laminar flow mode;

[0083] S3.3: Collect the formed nanofibers to obtain a preliminary separator;

[0084] Step 4: Double-sided solvent diffusion:

[0085] S4.1: DMAc (55% concentration) and DMSO (30% concentration) were selected as solvents;

[0086] S4.2: placing the nanofiber membrane in a diffusion device;

[0087] S4.3: DMAc was placed on the upper side of the membrane and DMSO was placed on the lower side, the evaporation rate was 0.45 mm / h, the ambient humidity was 32%, the diffusion temperature was 56 °C, and the diffusion time was 1.6 hours;

[0088] Step 5: Post-treatment: Wash with deionized water 4 times and dry at 63°C for 1.2 hours.

[0089] Comparative Example 1 (Traditional Method)

[0090] Step 1: Material preparation: Para-aramid purity: 99.5%, molecular weight: 120,000, temperature resistance: >200°C;

[0091] Step 2: Prepare para-aramid solution:

[0092] S2.1: Add NMP solvent to the reactor;

[0093] S2.2: Lower the solvent temperature to -8°C, add the para-aramid in three batches, and stir magnetically for 3 hours;

[0094] S2.3: After complete addition, heat to 58°C and continue stirring for 1.2 hours to form a uniform solution;

[0095] Step 3, preparation method: directly preparing the nanofiber membrane by conventional electrospinning method using the para-aramid solution without using microfluidic continuous printing technology;

[0096] Step 4: Traditional post-treatment: Wash with deionized water three times and dry at 62°C for 1.1 hours.

[0097] Comparative Example 2 (Traditional Method)

[0098] Step 1: Material preparation: Para-aramid purity: 99.8%, molecular weight: 150,000, temperature resistance: >200°C;

[0099] Step 2: Prepare para-aramid solution:

[0100] S2.1: Add NMP solvent to the reactor;

[0101] S2.2: Lower the solvent temperature to -6°C, add the para-aramid in three batches, and stir magnetically for 2.5 hours;

[0102] S2.3: After complete addition, heat to 56°C and continue stirring for 1.3 hours to form a uniform solution;

[0103] Step 3, preparation method: directly preparing the nanofiber membrane by conventional electrospinning method using the para-aramid solution without using microfluidic continuous printing technology;

[0104] Step 4: Post-treatment: Wash with deionized water 4 times and dry at 63°C for 1.2 hours.

[0105] The performance test and results are shown in Table 1:

[0106]

[0107]

[0108] The performance test results are obtained from Table 1, and the following analysis is performed:

[0109] Modulus: The modulus of Example 1 and Example 2 is higher than that of Comparative Example 1 and Comparative Example 2, reaching 15.2 GPa and 16.8 GPa respectively, while the modulus of Comparative Example 1 and Comparative Example 2 is only 10.5 GPa and 11.3 GPa. The difference between the examples and the comparative examples is that the examples have microfluidic continuous printing technology and double-sided solvent diffusion process flow, while the comparative examples do not have microfluidic continuous printing technology and double-sided solvent diffusion process flow, which indicates that the microfluidic continuous printing technology and double-sided solvent diffusion process can improve the mechanical properties of the diaphragm.

[0110] Thermal stability: Example 1 and Example 2 can still maintain structural integrity above 200°C without obvious performance degradation, while Comparative Example 1 and Comparative Example 2 have loose structures and obvious performance degradation at the same temperature, which indicates that the diaphragm prepared by the method of the present invention has better thermal stability.

[0111] Pore ​​size uniformity: Examples 1 and 2 have better pore size uniformity, with pore sizes of 45±5nm and 50±5nm, respectively, while Comparative Examples 1 and 2 have wider pore size distributions (40-80nm) and are uneven, which indicates that microfluidic continuous printing technology can accurately control the pore size.

[0112] Uniformity of membrane thickness: The membrane thickness uniformity of Example 1 and Example 2 is better, with thicknesses of 2.0±0.1μm and 2.1±0.1μm, respectively, while the thickness uniformity of Comparative Example 1 and Comparative Example 2 is poor, with thicknesses of 2.2±0.3μm and 2.3±0.4μm, respectively, which further demonstrates the advantages of microfluidic continuous printing technology.

[0113] Porosity and permeability of diaphragm: The diaphragms of Examples 1 and 2 have higher porosity (75% and 78%) and better permeability (120s / 100mL and 115s / 100mL), while the diaphragms of Comparative Examples 1 and 2 have lower porosity (68% and 69%) and poorer permeability (150s / 100mL and 145s / 100mL), which indicates that the method of the present invention can optimize the microstructure of the diaphragm and improve its performance.

[0114] Mechanical strength and liquid absorption rate: The diaphragms of Examples 1 and 2 have higher mechanical strength (250 MPa and 280 MPa) and higher liquid absorption rates (55% and 58%), while the mechanical strength and liquid absorption rates of Comparative Examples 1 and 2 are relatively low, which indicates that the diaphragms prepared by the method of the present invention have advantages in mechanical properties and electrolyte absorption capacity.

[0115] By comparing the performance test results of the embodiments and the comparative examples, it can be clearly seen that the method of the present invention has higher advantages than the comparative examples of the traditional method in preparing nanoporous aramid nanofiber diaphragms with high modulus and high thermal stability, and through microfluidic continuous printing technology and double-sided solvent diffusion process, the pore size and thickness of the diaphragm are precisely controlled, and the microstructure is optimized, thereby improving the mechanical properties, thermal stability and air permeability of the diaphragm. These advantages enable the diaphragm prepared by the method of the present invention to exhibit excellent structure and mechanical stability in high temperature environments, solving the shortcomings of traditional diaphragm materials and preparation processes.

[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nanoporous aramid nanofiber membrane with high modulus and thermal stability, characterized in that: The method comprises the following preparation steps: Step 1: Material preparation: Select para-aramid with a purity greater than 99% as the base material; Step 2, preparing a para-aramid solution: adding N-methylpyrrolidone solvent into a reaction kettle, and then adding the para-aramid into the reaction kettle in three batches, and performing a low-temperature solution polycondensation reaction to form a uniform para-aramid solution; Step 3: Formulate a microfluidic continuous printing strategy: construct a microfluidic continuous printing device, set the parameters of the microfluidic continuous printing device, perform printing, and obtain a preliminary nanofiber membrane; Step 4: Design a double-sided solvent diffusion process: build a double-sided solvent diffusion device, control the diffusion process parameters, perform double-sided solvent diffusion, and perform post-processing on the nanofiber membrane after completing the double-sided solvent diffusion; Step 5: Result analysis and optimization: Analyze the performance characteristics and existing problems of the nanofiber membrane based on the test results, and propose improvement measures to address the problems.

2. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The preparation process of the para-aramid solution in step 2: S2.1, adding N-methylpyrrolidone solvent into the reaction kettle; S2.2, lowering the solvent temperature to between -10°C and -5°C, adding the para-aramid in three batches, and carrying out a low-temperature solution polycondensation reaction for 2-4 hours under magnetic stirring; S2.

3. After the para-aramid is completely added, raise the temperature to between 55-60°C and continue to maintain magnetic stirring for 1-1.5 hours to form a uniform para-aramid solution.

3. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The microfluidic continuous printing device in step three includes a precision injection pump, a microfluidic chip and a collector. The parameters of the microfluidic continuous printing device are set as follows: the thickness of the nanofiber membrane is set between 1.8-2.2 μm with an accuracy of ±0.1 μm, the pore size of the nanofiber membrane is set between 40-60 nm with an accuracy of ±5 nm, the flow rate of the injection pump is set to 2-3 mL / h, the channel width of the microfluidic chip is set to 100-200 μm, and the channel depth of the microfluidic chip is set to 50-100 μm.

4. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The printing process in step 3: S3.

1. After the parameters of the microfluidic continuous printing device are set, the para-aramid solution is injected into the microfluidic chip through a syringe pump; S3.2, controlling the flow rate of the para-aramid solution between 45-55 μL / min, controlling the temperature between 55° C. and 60° C., controlling the pressure difference between 20 psi and 25 psi, and adopting a laminar flow mode to form nanofibers using microfluidic technology; S3.

3. Collect the formed nanofibers through a collector to obtain a preliminary nanofiber membrane.

5. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The double-sided solvent diffusion device in step 4 includes a solvent evaporation pool and a supporting substrate.

6. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The diffusion process parameters in step 4 are set as follows: the diffusion temperature is controlled between 55-60° C., and the diffusion time is controlled between 1.5-2 h.

7. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The diffusion process in step 4 is: S4.1, selecting N,N-dimethylacetamide and dimethyl sulfoxide as solvents; S4.2, placing the initially obtained nanofiber membrane in a double-sided solvent diffusion device; S4.

3. Place two different solvents of S4.1 on the upper and lower sides of the nanofiber membrane in the double-sided solvent diffusion device, and control the evaporation rate of the solvent to be between 0.3-0.5 mm / h, the evaporation direction of the solvent is perpendicular to the membrane surface, and control the ambient humidity to be between 30% and 40%.

8. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 7, characterized in that: The N,N-dimethylacetamide solvent is placed on the upper side of the nanofiber membrane, and the dimethyl sulfoxide solvent is placed on the lower side of the nanofiber membrane.

9. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 8, characterized in that: The concentration of the N,N-dimethylacetamide is 50% to 55%, and the concentration of the dimethyl sulfoxide is 30% to 35%.

10. The nanoporous aramid nanofiber membrane with high modulus and thermal stability according to claim 1, characterized in that: The post-treatment process in step 4 is as follows: after the double-sided solvent diffusion is completed, the nanofiber membrane is washed with deionized water for 2-5 times, and placed in an oven to dry at a temperature of 60-65° C. for 1-1.2 hours.